A influência das percepções do contexto institucional na moral tributária de empreendedores: evidências do setor de telecomunicações - Lima, Ricardo de (2022)
Taxation assumes a relevant role within entrepreneurship as it represents a tool that promotes resources that will promote economic and social development. However, this importance is not always recognized by entrepreneurs, which can legitimize tax evasion behavior. It is noteworthy that, before there is this effective behavior, there will always be an intrinsic and voluntary motivation to pay taxes, that is, its tax morale, which is influenced by several external factors, which may increase or reduce it. In view of this, the need to recognize which are these elements that influence this motivation of entrepreneurs emerges. For this, support is sought in institutional theory, in which it is recognized that institutions influence and are influenced by social actors (entrepreneurs), shaping their actions, attitudes and preferences. From this, the objective of the study is to recognize which are the elements that influence the tax morale of entrepreneurs. In order to carry out the research, a quantitative approach is used, through a survey using a structured questionnaire applied to a sample of 167 entrepreneurs in the telecommunications sector. For analysis purposes, Structural Equation Modeling (SEM) is performed using the technique of partial least squares (PLS), in which the explanatory variables are tested. The results indicate that the risk of detection, the severity of punishments and tax justice represent determining factors for the tax morale of entrepreneurs in the telecommunications sector. In addition, age also contributes to this motivation, indicating that the younger the entrepreneur, the lower his tax morale. Corruption assumes importance within the models tested, however with the inclusion of the age variable it loses significance. Therefore, this study contributes by presenting empirical evidence on institutional factors that guide the tax morale of entrepreneurs in the telecommunications sector, promoting contributions to the construction of reforms that improve the environment and correct institutional failures, thus contributing to the reduction of tax evasion.